2010
DOI: 10.1111/j.1399-0039.2010.01468.x
|View full text |Cite
|
Sign up to set email alerts
|

The profile of KIR3DL1 and KIR3DS1 alleles in an African American population resembles that found in African populations

Abstract: KIR3DL1 and KIR3DS1 allele frequencies were determined by DNA sequencing of the complete coding regions from 100 random unrelated African Americans. Alleles 3DL1 *01501 (29 individuals) and 3DL1*01502 (23 individuals) were most frequently observed in addition to 21 other known alleles and seven new alleles: KIR3DL1*01503, *03102, *064, *065, *066, *067, and *068. Two of the new alleles (KIR3DL1*064, *065) created additional variants of the chimeric KIR3DL1/KIR3DL2 gene. KIR3DS1*01301 (94% of the gene positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
14
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 22 publications
7
14
0
Order By: Relevance
“…The distribution of KIR3DL1 alleles in the study population resembled that previously reported in Japanese (16) and Chinese Han population in Zhejiang province (29). KIR3DL1*01502 was the most common allele in Chinese Han and Japanese populations with a frequency of more than 60%, which was significantly higher than in Irish (14.3%) (14) and African Americans (23%) (15). Other alleles also showed the similar distribution in the study southern Chinese and Japanese populations in the order of KIR3DL1*00501>3DL1*00701>3DL1*00101>3DL1*020.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…The distribution of KIR3DL1 alleles in the study population resembled that previously reported in Japanese (16) and Chinese Han population in Zhejiang province (29). KIR3DL1*01502 was the most common allele in Chinese Han and Japanese populations with a frequency of more than 60%, which was significantly higher than in Irish (14.3%) (14) and African Americans (23%) (15). Other alleles also showed the similar distribution in the study southern Chinese and Japanese populations in the order of KIR3DL1*00501>3DL1*00701>3DL1*00101>3DL1*020.…”
Section: Discussionsupporting
confidence: 78%
“…In sharp contrast to the highly diversified KIR3DL1 the polymorphism of 3DS1 is rather conserved. In fact most populations share the same predominant KIR3DS1 allele: KIR3DS1*01301 (14,15,16,17). The present study also identified KIR3DS1*01301 as the predominant KIR3DS1 allele in southern Chinese.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations